Functional morphology of the tubular genital organs in the female owl monkey (Aotus spp.). Issue 3 (9th March 2015) - Mayor, Pedro; Takeshita, Rafaela Sayuri Cicalise; Coutinho, Leandro Nassar; Sánchez, Nofre; Gálvez, Hugo; Ique, Carlos; Ruiz, Julio Cesar; Monteiro, Frederico Ozanan Barros
Abstract Background Studies on reproductive morphology are important to understand the reproductive cycle of non‐human primates. Methods This study describes the functional morphology of the adult female tubular genital organs in 41 Aotus (12.8 ± 6.8 years old, ranging from 3 to 25 years), with respect to reproductive status and number of parturitions. Results In females with developing embryos, endometrial glands showed a higher secretion than other females, and the embryo implantation occupied this secretive endometrium. Changes in the thickening, number of layers, and keratinization in the vaginal epithelium suggest that vaginal cytology may be an indicator of the estrous cycle. Non‐pregnant multiparous females had a larger uterine body than nulliparous females. Number of parturitions and reproductive state had an impact on tubular genital organs in female owl monkeys. Conclusions These results can be useful for the development of biotechnologies of reproduction and for improvement of the management of this species.